2022
DOI: 10.1088/1361-665x/ac775d
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive genetic algorithm enabled tailoring of piezoelectric metamaterials for optimal vibration attenuation

Abstract: Piezoelectric metamaterials with shunt resonant circuits have been extensively investigated for their tunability in bandgaps. However, the vibration attenuation ability induced by the electromechanical coupling is generally weaker than that of mechanical metamaterials, limiting their applications in engineering practice. This research presents a non-uniform piezoelectric metamaterial beam with shunt circuit parameters optimized by an adaptive genetic algorithm for tailoring the vibration attenuation zone. Firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…The small frequency spacing in Figure 2(a) yields a wider overall bandgap region as compared to the unsuccessful aggregation with the completely separated adjacent bandgaps in Figure 2(c) under larger frequency spacing. In addition, as previous studies have indicated, using load resistor R can suppress those sharp local resonant peaks to achieve a continuous attenuation region [17,18]. However, the smoothed bandgap by adequately tuning the load resistance R results in a pseudo bandgap where the transmission ratio becomes large, i.e., at around -10dB (around 0.3) for wave attenuation [13,14,18].…”
Section: Design Strategy Of Adaptive Broadband Wave Attenuationmentioning
confidence: 93%
See 3 more Smart Citations
“…The small frequency spacing in Figure 2(a) yields a wider overall bandgap region as compared to the unsuccessful aggregation with the completely separated adjacent bandgaps in Figure 2(c) under larger frequency spacing. In addition, as previous studies have indicated, using load resistor R can suppress those sharp local resonant peaks to achieve a continuous attenuation region [17,18]. However, the smoothed bandgap by adequately tuning the load resistance R results in a pseudo bandgap where the transmission ratio becomes large, i.e., at around -10dB (around 0.3) for wave attenuation [13,14,18].…”
Section: Design Strategy Of Adaptive Broadband Wave Attenuationmentioning
confidence: 93%
“…T is the transformation matrix of propagating wave of the th i non-uniform unit cell. The overall transmission ratio is defined as the ratio of the displacement of the transmitted wave to the displacement of the incident wave [14,15,17], given as, 1) and (2).…”
Section: Modeling Of Graded Piezoelectric Metamaterials Beammentioning
confidence: 99%
See 2 more Smart Citations
“…geothermal [1], solar [2] and tidal energies [3]) to reduce the usage of fossil energy. Ubiquitous vibrational energy [4][5][6] has great potential as the sustainable energy source for lowpower electronics [7]. Three major energy harvesting methods have been proposed to convert vibrations into electricity, namely, electromagnetic [8][9][10], piezoelectric [11][12][13][14] and triboelectric transductions [15][16][17].…”
Section: Introductionmentioning
confidence: 99%